2008
DOI: 10.1007/s10067-008-1056-0
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for cardiovascular disease and endothelin-1 levels in Takayasu arteritis patients

Abstract: The objective of this study was to evaluate traditional risk factors for cardiovascular disease (CVD) and endothelin-1 (ET-1) levels in Takayasu arteritis (TA) patients. Twenty-two TA patients and 37 controls were evaluated. TA patients had a higher prevalence of hypertension (63.6% vs. 21.6%, p=0.001) and higher levels of triglycerides (129.5 mg/dL+/-70.8 vs. 88.4 mg/dL+/-60.8, p=0.017) than controls. Mean number of CVD risk factors was 1.64+/-1.22 in TA patients and 1.03+/-1.44 among controls, p=0.030. More … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…In an experimental study, co‐exposure to O 3 plus PM 2.5 induced acute decreases in BP in all rats (Wagner et al, ). SO 2 , NO 2 , or PM 2.5 exposure causes a decrease in antioxidant defenses (Liu et al, ) and dysregulation of the NO synthase pathways, which induced the production of the vasoconstrictor ET‐1 (Bouthillier et al, ; Vincent et al, ; Weis and Cooke, ; de Souza et al, ). Additionally, epidemiological studies suggest that proinflammatory cytokines, including tumor necrosis factor‐α (TNF‐α), inducible nitric oxide synthase (iNOS), cyclooxygenase‐2 (COX‐2), and interleukin‐6 (IL‐6), are abnormal in patients with congestive heart failure (CHF) and myocardial infarction ( Mann, ; Yndestad et al, ; Yun et al, ; Han et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In an experimental study, co‐exposure to O 3 plus PM 2.5 induced acute decreases in BP in all rats (Wagner et al, ). SO 2 , NO 2 , or PM 2.5 exposure causes a decrease in antioxidant defenses (Liu et al, ) and dysregulation of the NO synthase pathways, which induced the production of the vasoconstrictor ET‐1 (Bouthillier et al, ; Vincent et al, ; Weis and Cooke, ; de Souza et al, ). Additionally, epidemiological studies suggest that proinflammatory cytokines, including tumor necrosis factor‐α (TNF‐α), inducible nitric oxide synthase (iNOS), cyclooxygenase‐2 (COX‐2), and interleukin‐6 (IL‐6), are abnormal in patients with congestive heart failure (CHF) and myocardial infarction ( Mann, ; Yndestad et al, ; Yun et al, ; Han et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Takayasu arteritis (TAK) is a chronic inflammatory disease that mainly involves the aorta and its major branches [ 1 ]. Previous studies reported higher prevalence of traditional cardiovascular risk factors in patients with TAK than in healthy controls [ 2 4 ]. Moreover, accelerated atherosclerosis has been clearly documented in TAK [ 5 , 6 ], and the incidence of cardiovascular events is higher in patients with TAK than in age- and sex-matched controls [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the majority of papers, patients with active disease presented with higher ESR and CRP levels as compared with patients with stable/inactive disease (ESR ranged 5–115 mm/hour vs 1–43 mm/hour and CRP ranged 0.1–99.1 mg/dL vs 0.06–7.77 mg/dL for active vs stable disease, respectively). Nevertheless, 28.5% of patients classified as being in remission (National Institutes of Health (NIH) criteria) may present with elevated CRP and 23.8% with elevated ESR23 (overall LoE 4) 23–29…”
Section: Resultsmentioning
confidence: 99%